Sistem Pemantauan Kesehatan Kambing Berdasarkan Suhu Tubuh dan Detak Jantung Berbasis Internet of Thing - Sibarani, Yohana Oktavia; Rismawan, Tedy; Nirmala, Irma (Journal of Computer System and Informatics (JoSYC), 2024)
The goat is one of the species of livestock that has many benefits. Goat benefits become one of the important aspects of keeping goats healthy. Predicting diseases in goats is quite difficult because of the lack of medical experts in the field to check the health condition of the goats. The research has created a system that can determine the health of goats based on their body temperature and heart rate. The system is designed to make it easier for farmers to monitor their health and perform early treatment when there are sick goats. The data used in this study is the normal body temperature and heart rate of the goat. This research uses NodeMCU as a microcontroller and also a sensor. The sensors used are the DS18B20 temperature sensor and the MAX30102 heart rate sensor. The system can measure both temperature and heart rate at the same time. The test results showed an average data error on the measurement of the DS18B20 sensor and the MAX30102 sensor. In these measurements, the average error of the sensor was 0.77% and the sensor MAX30102 was 2.23%. The data from the monitoring of this sensor will be displayed on the website so that it can be viewed by the user.